2018
DOI: 10.2147/idr.s145027
|View full text |Cite
|
Sign up to set email alerts
|

Majocchi’s granuloma: current perspectives

Abstract: Majocchi’s granuloma (MG) is a rare fungal infection of the dermis that is mainly caused by dermatophytes (in ≥95% of cases); the most frequently identified cause is anthropophilic Trichophyton rubrum. In the rest of the cases, the causes are non-dermatophytic fungi such as Aspergillus species. This review aimed to provide information about the current perspectives on MG regarding its clinical characteristics, predisposing factors, laboratory diagnosis, and treatment strategies. Although the lower extremities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
77
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 70 publications
5
77
1
9
Order By: Relevance
“…The second type is subcutaneous nodules that usually happens in immunosuppressed hosts and in the upper limbs, clinical manifestations characterized by groups of nodules [1]. Trichophyton rubrum is the most common cause of Majocchi's granuloma, followed by Trichophyton mentagrophytes, Trichophyton violaceum, and Trichophyton tonsurans [2]. In this case report, an immunocompetent patient developed nodules after trauma and we confirmed that the pathogen was Trichophyton tonsurans.…”
Section: Introductionsupporting
confidence: 65%
“…The second type is subcutaneous nodules that usually happens in immunosuppressed hosts and in the upper limbs, clinical manifestations characterized by groups of nodules [1]. Trichophyton rubrum is the most common cause of Majocchi's granuloma, followed by Trichophyton mentagrophytes, Trichophyton violaceum, and Trichophyton tonsurans [2]. In this case report, an immunocompetent patient developed nodules after trauma and we confirmed that the pathogen was Trichophyton tonsurans.…”
Section: Introductionsupporting
confidence: 65%
“… 72 T. rubum is the most common causative organism, followed by T. interdigitale , T. violaceum , and T. tonsurans . 72 , 73 Majocchi granuloma typically presents as inflammatory perifollicular papules or pustules, mainly on the face or limbs ( Figure 4 ). 24 , 73 , 74 Nodular lesion and subcutaneous abscess are more commonly seen in immunocompromised individuals.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…The underlying mechanisms of the pathogenesis of MG are not well known, although some hypotheses have been advanced, all based on host‐ and microorganism‐related factors. The first and most important host‐related factor is trauma of the skin due to shaving or scratching, that along with immunosuppression are believed to cause fungal invasion …”
mentioning
confidence: 99%
“…Painful nodules also mimic erythema nodosum, thrombophlebitis, and erythema induratum of Bazin. In immunosuppressed patients, it is important to distinguish MG from some tumoral diseases such as Kaposi sarcoma and lymphoma …”
mentioning
confidence: 99%